Comparative analysis of game-related parameters and team performance across European men's volleyball leagues - Ašcic, S.; Marinovic, M.; Kuna, D.; Curic, M.; Šklempe Kokic, I. (Studia Sportiva, 2025)
Game-related parameters play a direct role in distinguishing between winning and losing volleyball teams, directly influencing league rankings. PURPOSE: This study aimed to assess the impact of serve, reception, attack, and block parameters on higher and lower-quality leagues, while also examining their influence on league rankings. METHODS: Data from men`s volleyball matches in higher-quality leagues spanning from 2012/13 to 2022/23 seasons in Italy, Poland, and Turkey, and matches in lower-quality leagues spanning from the 2018/19 to 2022/23 seasons in the Czech Republic and Belgium, were analysed, totalling 820,769 points. The study compared league rankings across all leagues and evaluated serve, reception, attack, and block parameters for effectiveness and errors. RESULTS: Higher-quality leagues demonstrated a significantly greater number of points won through attacks (p=0.00), perfect reception (p=0.00), and errors during the reception (p=0.00), as well as a lower number of points, won through serving (p=0.03), attacking errors (p=0.00), and points won through blocking (p=0.00) compared to lower-quality leagues. No significant differences were observed in serving errors (p=0.82). When comparing league rankings, statistically significant differences were found in the number of points won through serving (p=0.00), points won through attacking (p=0.00), points won through blocking (p=0.00), reception errors (p=0.00), and attacking errors (p=0.00). CONCLUSION: Our findings underscore the nuanced relationship between skill execution, tactical decisions, and competitive level, emphasizing the distinct performance strategies employed by higher-quality and lower-quality leagues. Expanding future research to include additional leagues and performance variables will provide a more comprehensive understanding of the factors influencing team success.